VLBI Imaging of Parsec-scale Radio Structures in Nearby Low-luminosity Active Galactic Nuclei - Xiaopeng Cheng; Tao An; Willem A. Baan; Ranieri D. Baldi; David R. A. Williams-Baldwin; Bong Won Sohn; Robert Beswick; Ian M. McHardy (The Astrophysical Journal Supplement Series)
We report the results of high-resolution 5 GHz Very Long Baseline Array and European VLBI Network observations of 36 nearby galaxies, an extension of the Legacy e-MERLIN Multi-band Imaging of Nearby Galaxies survey. Our sample includes 21 low ionization nuclear emission regions, four Seyferts, three absorption line galaxies, and eight H ii galaxies. We achieved an unprecedented detection rate, successfully imaging 23 out of 36 sources with a detection threshold of ∼20 μ Jy beam ^−1 . The radio sizes are typically of ≤5 pc. Core identification was achieved in 16 sources, while seven others were identified as core candidates. Radio luminosities of the sample range from 10 ^34 to 10 ^38 erg s ^−1 . Our analysis reveals a predominance of compact core structures, with 10 sources exhibiting a one-sided core jet morphology and NGC 2146 exhibiting a rare two-sided jet structure. The study advances our understanding of the compactness of radio sources at various scales, indicating a core-dominated nature in all but one galaxy, NGC 2655. We find moderate to strong correlations between radio luminosity, black hole (BH) mass, optical [O iii ] line luminosity, and hard X-ray luminosity, suggesting a common active galactic nucleus (AGN) core origin. These results provide new insights into the fundamental plane of BH activity and support the role of the synchrotron process in low-luminosity AGN radio emission.